Stress-and-coping of Chinese repatriate scholars. - Wu, Li. (2013)
The returned overseas-educated Chinese scholars are a driving force behind the rapid Chinese education and technology development. Despite the drastically increasing number of Chinese repatriate scholars, little is known about their experience of re-entry into China and how they readjust to the work and family life in a changed homeland. Their emphasis of pursuing world class scholarship and their traditional value of the family led to the design of the present study that involved both the individual, person within the family and the family level analysis of stress and coping upon re-entry. Study 1through qualitative interviews explored their subjective multiculturalism and their perceived stressors and coping responses. Study 2 tested the effectiveness of various stress, coping styles/strategies and a hypothesized moderating effect of coping flexibility at the individual level. Study 3 focused on the family, and examined how perceived family resilience affected individual’s coping efficacy and the collective stress and coping experiences with the family as a unit of analysis upon reentry. Results were discussed for policy input to further facilitate the repatriate scholars readjustment.